The phenolic faction of Italian extra virgin olive oils: eluciadation through combined liquid chromatography and NMR approaches - Klikarová, Jitka; Rotondo, Archimede; Cacciola, Francesco; Česlová, Lenka; Dugo, Paola; Mondello, Luigi; Rigano, Francesca (Springer, 2019)
Extra virgin olive oils (EVOOs) contain various bioactive compounds belonging to phenol family. These compounds are traditionally determined by liquid chromatography, despite such a method implies some issues that have to be taken into account. Therefore, our study was focused on the employment of reversed-phase high-performance liquid chromatography coupled to diode array detection and electrospray ionisation mass spectrometry (RP-HPLC-DAD/ESI-MS) and nuclear magnetic resonance (NMR) approaches, which are here compared in order to provide thorough information about the phenol profile in EVOOs. Data comparison led to matching results with some experimental divergence as expected from a challenging coupled analysis concerning dynamically unstable compounds. Specific concerns of both techniques are described shedding light on the potential advantages arising from the employment of the quick NMR and short and sensitive HPLC analysis. This is the first step toward a joined approach for the future analysis of the phenolic profile.
Fenolická frakce italských extra panenských olivových olejů: zhodnocení pomocí kombinované kapalinové chromatografie a NMR
Keywords: Extra virgin olive oils (EVOOs); Phenols; HPLC; DAD; ESI-MS; NMR; Extra panenský olivový olej; fenoly; HPLC; DAD; ESI-MS; NMR